MEKANISME PENGENDALIAN OLEH MANAJEMEN DAN PERAN KOMITE MEDIS DALAM PENERAPAN INA CBG PADA PASIEN JAMKESMASDI RS PKU MUHAMMADIYAH TEMANGGUNG (RS Type C) Studi Kasus Sectio Caesaria - , MIN ADADIYAH; , DR. Julita Hendrartini, drg, M.Kes, AAK. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Reformed direction of health financing system based on social health insurance is, at the moment, considered as the most relevant for Indonesia. Managed care is supposed to maintain accountability and control cost. One of the characteristics is prospective payment system using DRG. The success of DRG implementation partly depends on human resources and the management that understands technique of implemention, methods of monitoring and control. Objective: The objective of the study was to identify control mechanism of the management and role of medical committee in the implementation of INA-DRG or INA-CBG. Method: The study was descriptive case study. The qualitative data (obtained from indepth interview with vice director, managers, medical committee and the secretary, and internal Jamkesmas control team in hospital as well as staff of INA- CBG) and quantitative data (available at unit of medical records and finance). Result: Average cost of minor sectio caesaria (SC) was Rp 2,902,383 and medium SC Rp 2,701.075. Tariff of INA-CBG for minor SC was Rp 1,230,429 and medium SC Rp 1,365,964. Tariff-based cost at PKU Muhammadiyah was 235% higher than INA-CBG tariff for SC minor and 197% higher for medium SC. Average length of stay (ALOS) of INA-CBG for patients with minor SC was 5.55 days whereas for those with medium SC was 5.64 days. Actual ALOS at PKU Muhammadiyah Hospital Temanggung was 8.21 for patients with minor SC and 8.28 for those with medium SC. ALOS of patients with minor SC at PKU Muhammadiyah Hospital was 148% higher than ALOS of INA-CBG for SC of hospital type C. Conclusion: Management of control mechanism and role of medical committee in the implementation of INA-CBG for Jamkesmas patients at PKU Muhammadiyah Hospital Temanggung was not yet effective. There was no control of cost in patients with SC intervention. Medical committee had not actively involved in the implementation of INA-CBG at PKU Muhammadiyah Hospital Temanggung in aspect of quality control in patients with SC intervention.